2016
DOI: 10.1017/s1431927616001574
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differences in Amorphous Layer Formation during FIB Sample Preparation between Metals and Non Metals

Abstract: Over the last decade dual beam FIB has proved increasingly useful in a laboratory setting. Researchers have used dual beam FIB's in a wide variety of experiments, including but in no way limited to fabrication of nano pillars for micromechanical testing, modification of circuits during use, and the creation of tooling for nanoscale machining. The field of high resolution microscopy in particular has seen huge benefits from FIB processing in the form of high quality orientation specific lamella. One drawback of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Amorphised layers induced by ion beam milling have been reported in several studies using both TEM and EBSD (electron backscatter diffraction) 24,40,41 . For example, Presley et al reported an amorphised layer with a similar 4 nm thickness for a 30 kV Ga + FIB milling of Al7075 29 . Kelley et al 42 compared amorphisation for Si between Ga + and Xe + and found Xe + ions created a thinner amorphous layer, consistent with our results although the layers were much larger (21.5 nm with Ga + 42 ) due to the nature of covalent bonds of Si and faster migration of ion‐induced lattice defects in Al 43 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Amorphised layers induced by ion beam milling have been reported in several studies using both TEM and EBSD (electron backscatter diffraction) 24,40,41 . For example, Presley et al reported an amorphised layer with a similar 4 nm thickness for a 30 kV Ga + FIB milling of Al7075 29 . Kelley et al 42 compared amorphisation for Si between Ga + and Xe + and found Xe + ions created a thinner amorphous layer, consistent with our results although the layers were much larger (21.5 nm with Ga + 42 ) due to the nature of covalent bonds of Si and faster migration of ion‐induced lattice defects in Al 43 …”
Section: Resultsmentioning
confidence: 95%
“…pillars and found that Xe + ‐prepared pillars had higher yield strengths than Ga + ‐prepared pillars because it avoided Ga segregation on the grain boundary that reduced the strength of polycrystalline aluminium pillars. However, questions remain as to the suitability of Xe + pFIB for the preparation of Al alloy TEM specimens, such as compositional contamination, structural changes (eg new phases), 26,27 ion‐induced damage (eg dislocation loops), 28 and amorphisation, 2,29,30 Xe ‘bubble’ or precipitate formation, 27,31,32 as well as levels of redeposition 5 , 14 …”
Section: Introductionmentioning
confidence: 99%